'I praie ye send for the courall' children's coral as the physical embodiment of parental hopes and fears in early modern England - Richards, Francesca Elizabeth (The history of the family : an international quarterly, 2024)
Mediterranean red coral has long been believed to be imbued with sacred, spiritual and healing power and was given to children across Europe in the form of an amulet, teether or medicine. In early modern England, portraits of children from affluent families and medical receipts provide snapshots of coral usage, a moment in time, which do not adequately reveal the spiritual, therapeutic and affective significance of this material within the context of unique family circumstances and a multitude of perceived threats to children's health. Focusing on five case studies, this article delves into the lived experience of families who deemed coral objects an essential childhood accessory in the period from 1590 to 1775. Julian Herrick, a goldsmith's widow, Sir John Oglander, a knight caught up in the civil war, Dr Garencières, a doctor confronting dangerous infection, Lady Blackett, a devoted grandmama, and Ann Lord, a woman facing destitution, all placed value on coral for their young children. This study draws on a diverse range of material and documentary evidence from the seventeenth and eighteenth century to unpack the significance of red coral for parents within a changing religious, political and medical landscape. Building on scholarship within material culture studies and the history of emotions, this study also situates children's coral objects within emotional relationships and seeks to uncover the implicit meanings such objects held which could not be written or articulated due to illiteracy, controversy or persecution. By combining a micro-historical approach with a broader thematic analysis, the case studies presented indicate that coral occupies an important place in the history of the early modern family as the embodiment of the anxieties of parents and grandparents, a means to soothe and protect young children and a material expression of hope, love and faith, particularly during periods of crisis and separation